Istikhdāmu al-Ṭarīqah al-Īhāiyah wa Fa’āliyatuhā fī Tanmiyati Mahārati al-Kalām ‘alā Ṭalabati Jāmi’ati Maulānā Mālik Ibrāhīm al-Islāmiyah al-Hukūmiyah Malang - Jumriyah, Jumriyah (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2020)
The Suggestopedia method consists of a series of recommendations based on the education of the science of suggestion described by Lozanov that suggestion is